Development of loop-mediated isothermal amplification technique for detection of Candida glabrata - Hassan, Yahaya (2020)
The increasing emergence of systemic fungal infections directly correlates with the growing population of immunocompromised groups. Candida glabrata is increasingly essential, due to rising isolation frequency and resistance development to antifungals. The diagnostic sensitivity of microbial culture (“gold standard”) method could miss up to 50% of the invasive candidiasis (IC) patients. Molecular diagnosis, particularly conventional PCR, is promising in diagnosing many infections, but sometimes limited in sensitivity, cost of the thermal cycler, and lack of quantification ability. The need to develop a sensitive, specific, and non–machine-dependent method that operates at isothermal temperature is imperative for prompt management and excellent clinical outcome. The study, therefore, developed the loop-mediated isothermal amplification (LAMP) method integrated with lateral flow immunoassay (LFA) techniques for point of care testing (POCT) detection of C. glabrata. Internal transcribed spacer (ITS) ribosomal DNA of C. glabrata ATCC 2001 reference strain was cloned to form a recombinant plasmid (pUC19-ITS) as a standard for LAMP assay evaluation. Three pairs of LAMP primers (FIP/BIP, F3/B3 and LF/LB) were designed, optimised, and evaluated to determine LAMP assay's sensitivity and specificity. The LF/LB were labelled with digoxigenin and biotin respectively for LFA. The detection limit of LAMP using 10-fold serial dilutions of recombinant plasmid and blood spiking experiment was conducted. The LAMP assay was optimised and evaluated using LFA test strip. The expected size of the recombinant plasmid was confirmed by linearisation with KpnI enzyme. Amplicon size (1049 bp) confirmed using M13 primers. The LAMP detection limit demonstrates the high sensitivity of 2.25 × 10-0 copies/μL with 1000 – fold compared to conventional PCR that indicates 2.25 × 103 copies/μL. The LAMP assay analysis of DNA from spiked blood indicates a range of detection limit between 106-101 CFU/mL using gel electrophoresis analysis. The PCR range detection limit was 106-105 CFU/mL. Thus, LAMP also shows 104– fold better performance. The LAMP specificity assay accurately detected C. glabrata with no cross-reactivity with other Candida or mould clinical isolates tested. The developed LAMP assay offers a rapid, simple, sensitive, and specific molecular test for C. glabrata detection. It would be a useful tool speeding management of C. glabrata invasive candidiasis patients through POCT approach.